Facilitating facilitators to facilitate—Some general comments on a strategy for knowledge implementation in health services - Eldh, Ann Catrine; Hälleberg-Nyman, Maria; Joelsson-Alm, Eva; Wallin, Lars (Frontiers in Health Services, 2023)
Numerous endeavours to ensure that day-to-day healthcare is both evidence-based and person-centred have generated extensive, although partial, comprehension of what guarantees quality improvement. To address quality issues, researchers and clinicians have developed several strategies as well as implementation theories, models, and frameworks. However, more progress is needed regarding how to facilitate guideline and policy implementation that guarantees effective changes take place in a timely and safe manner. This paper considers experiences of engaging and supporting local facilitators in knowledge implementation. Drawing on several interventions, considering both training and support, this general commentary discusses whom to engage and the length, content, quantity, and type of support along with expected outcomes of facilitators’ activities. In addition, this paper suggests that patient facilitators could help produce evidence-based and person-centred care. We conclude that research about the roles and functions of facilitators needs to include more structured follow-ups and also improvement projects. This can increase the speed of learning with respect to what works, for whom, in what context, why (or why not), and with what outcomes when it comes to facilitator support and tasks.